LANGUAGE CHOICE AND LANGUAGE ATTITUDE IN BATAK TOBA COMMUNITIES AT DUSUN TANI MAKMUR, DESA TELUK PULAI DALAM, KUALUH LEIDONG, KABUPATEN LABUHANBATU UTARA - Rekha Samaria Manalu; Nurhayati Sitorus; Febrika Dwi Lestari (Jurnal Scientia, 2023)
The aim of this research is to find out how language choices and language attitudes manifest in the speech community in Tani Makmur Hamlet, Kualuh Leidong District, North Labuhanbatu. To uncover the root of the problem, this research uses a sociolinguistic approach, using qualitative and quantitative methods. Data sources were obtained from speech events in the family domain, friendship domain, religion domain, education domain, and work domain. The techniques used to process data are observation methods, questionnaires, documentation. The data that has been successfully provided and classified is then explained clearly and then analyzed. The findings of the research on language choice are divided into 3 parts, namely teenagers, adults, parents and show that there are three language codes that are dominantly used by the Batak community in Teluk Pulaui Dalam village, the three codes are the Indonesian (BI) code, the Batak language code (BB), and Malay Language Code (BM). In language selection, among adults, Indonesian (BI) has a high percentage in the friendship domain around (64%), among teenagers, Indonesian (BI) has a high percentage in the employment domain around (98%), among parents, language Batak (BB) has a high percentage in the domain family area (100%), while in the choice of language the Batak community in Tani Makmur Hamlet, Teluk Pulai Dalam still has a positive attitude towards the Batak Toba language in Tani Makmur Hamlet, Kualuh Leidong District, North Labuhanbatu.